PENDIDIKAN ILMU PENGETAHUAN SOSIAL DI ERA SOCIETY 5.0 DALAM PERSPEKTIF ISLAM - Bayu (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
The Society 5.0 era has brought fundamental changes across various aspects of human life, including the field of education. Social Studies (IPS) education, as a discipline responsible for shaping students' social awareness and civic competencies, is required to adapt to a new reality characterized by the integration of the physical and digital worlds. The Islamic perspective in Social Studies education offers an integral approach that not only develops intellectual and social abilities but also nurtures spirituality and noble character. This article comprehensively discusses the challenges, opportunities, and implementation strategies of Social Studies education in the Society 5.0 era by integrating Islamic values. This study employs a qualitative literature review method with thematic analysis of various relevant sources. The discussion results highlight the importance of developing Social Studies education based on the values of monotheism (tawhid), social justice, and Islamic digital ethics as the foundation for building a competitive and morally upright generation.